FRAUD ANALYSIS IN THE MANAGEMENT OF VILLAGE FUNDS VIEWED FROM THE PERSPECTIVE OF THE HEXAGON THEORY - Wakik; Makayanawati; Puji Handayati (PENANOMICS: International Journal of Economics, 2023)
This study aims to analyze the influence of stimulus, ability, collusion, opportunity, rationalization and arrogance on fraud. This research was conducted in the Sumenep district. The number of samples in this study was 93 respondents, determined using the slovin formula. Data collection was carried out through a questionnaire. The data analysis technique used in this study is multiple linear regression. Based on the results of the analysis, it can be seen that the stimulus has a positive effect on fraud, capability hurts fraud, collusion has a positive impact on fraud, the opportunity has a positive effect on fraud, rationalization has a positive impact on fraud, and arrogance has a positive effect on fraud.